A biomechanical comparison of the grab, swing and track starts in swimming - Breed, R. V. P.; McElroy, G. K.; Young, W. B. (2001)
The study aimed to establish the effectiveness of the grab, swing and rear-weighted track starts in swimming. In order to minimise bias of prior learning, twenty-three non-competitive swimmers participated in the study (mean age 19.9 ± 2.4 yrs). Participants learned the techniques for 30 minutes weekly for an eight-week period. Testing involved two maximal trials of each technique in random order. Horizontal and vertical force components by the feet were measured using a Kistler force plate, and by the hands via a hand-bar instrumented with load cells. Video was used to measure temporal and kinematic variables. Analyses of variance and post-hoc tests were performed for each dependent variable. Significant differences were found between the grab and track starts in flight distance, take-off velocity and take-off angle, and between the swing and track starts in block time, total time and take-off velocity. Other than block time, the grab and swing starts were very similar in performance. No significant differences were found between any of the starts in flight time or entry angle. Almost all of the horizontal drive came from the legs during the grab start, with little arm contribution. In contrast, the arms contributed just over one-third of the total horizontal impulse in the track start and considerably more vertical impulse than the grab start. Results of the current study demonstrated a greater effectiveness of the track start over the grab and swing starts.